THE INFLUENCE OF WORK ENVIRONMENT AND WORK STRESS ON EMPLOYEE PERFORMANCE IN THE GENERAL SECTION (RECTORATE) AT UPN VETERANS, EAST JAVA - Muhkhamad Edris; Rifki Suwaji (Jurnal Ekonomi, 2023)
PN Veteran East Java is one of the Indonesian state universities located in Surabaya, East Java. In 2014, UPN "Veteran" East Java underwent a change in institutional status from a private university to a state university. Employee performance tends not to meet the desired targets. The General Section (Rectorate) of UPN Veterans East Java, targets the performance of employees to reach at least 75%. This is what causes employees to experience a lot of stress because employees have to meet targets and work under pressure. So based on the existing problems, the researcher is interested in conducting research entitled: "The Influence of the Work Environment and Work Stress on the Performance of General Section employees (Rectorate) at UPN Veterans East Java".This type of research uses quantitative research. The sample in this study were all employees of the General Section (Rectorate) at UPN Veterans East Java. The sampling technique uses the slovin formula. Data collection techniques using questionnaires and documentation. Data analysis techniques usingClassical Assumption Test, Normality Test, Multicollinearity Test, Linearity Test.Multiple Linear Regression Analysis, Coefficient Delta Test (∆r2).The results of the study indicate that there is a positive influence of perceptions of the work environment on employee performance. This is evidenced by the statistical results of the t test for work environment variables with a significance value of 0.000 less than 0.05 (0.000 <0.05), with a calculated t value of 6.834 greater than t table 1.999 (-6.834 <1.999) and a coefficient regression has a positive value of 0.676. The results of this study indicate that there is a negative effect of work stress on employee performance. This is evidenced by the statistical results of the t test for the work stress variable with a significance value of 0.544 greater than 0.05 (0.544> 0.05), with a calculated t value of 0.61 less than t table 1.999 (0.61 <1.999 ) and the regression coefficient has a negative value of 0.092.